The Palomas and Gavilanes: Gender in the Sainetes of Alberto Vacarezza - Castro, Donald S. (Latin American Theatre Review, 2004)
Alberto Vacarezza is one of the most prolific and popular of saineteros: his works mark both the rise and the decline of the genre and he greatly influenced the popular image of life in 1920s and 1930s in the porteño conventillo. This article presents how Vacarezza portrays gender issues and the role of women in the changing environment of the city of Buenos Aires. (DSC)